Lungworm infections in small ruminants in uşak province - Ercan Erot; Mustafa Kose (Eurasian Journal of Veterinary Sciences)
Aim: This study was carried out to determine the prevalence of lungworm infections in small ruminants in the Uşak province. Materials and Methods: The study was carried out by testing the stool samples of 250 sheep and 250 goats collected from 5 different localities in the Uşak province using the Baermann-Wetzel method. Results: While the prevalence of lungworm infections was 9.6% in sheep, it was 34.4% in goats. The prevalence of infection was found to be 22% in all sheep and goats. While the prevalence of lungworm infections in sheep was determined to be 9.8% in females, no infection was found in males. The prevalence of infection in goats was determined as 33.3% in females and 53.8% in males. The prevalence of Muellerius capillaris was 5.6%, Dictyocaulus filaria 2%, Protostrongylus sp. 1.2% and Cystocaulus ocreatus 0.8% in sheep. In goats, the prevalence of M. capillaris was 34.4% and C. ocreatus was 0.4%. Mix infections caused by two lungworm species were detected in three sheep. However, mix infection was detected in only one goat. When the prevalence of lungworm infection in sheep was compared according to breeds, infection was detected in two of the five sheep breeds. The prevalence of lungworm infection was 14.1% in Eşme breed sheep and 9.1% in Kıvırcık breed sheep. Conclusion: The prevalence and risk status of lungworm infections in small ruminant breeding have been demonstrated. In addition, it has been determined that raising sheep and goats together and grazing animals from different age groups together may pose a risk in terms of lungworm infections.